2009
DOI: 10.1038/jhh.2009.85
|View full text |Cite
|
Sign up to set email alerts
|

Despite evidence-based guidelines, systolic blood pressure remains inadequately controlled in older hypertensive adults

Abstract: We aimed to assess the trends in the prevalence, awareness, treatment and control of hypertension in Finnish men and women aged 60-74 years. Three independent cross-sectional population surveys were conducted in 1997, 2002 and 2007 remained stable. The mean diastolic blood pressure (BP) decreased in both genders. Awareness of hypertension increased from 60 to 71% in men (Po0.001 for trend) and from 66 to 76% (P ¼ 0.012) in women. The prevalence of antihypertensive drug treatment among hypertensive people inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 43 publications
3
6
0
Order By: Relevance
“…Better hypertension control, especially among elderly people, might provide the benefit of reducing the pace of other degenerative processes (29). Similar improvements in hypertension management and control that are demonstrated in this study have been shown in other settings such as in the UK (30) and Finland (31). The improvements are not only observed in developed settings.…”
Section: Discussionsupporting
confidence: 88%
“…Better hypertension control, especially among elderly people, might provide the benefit of reducing the pace of other degenerative processes (29). Similar improvements in hypertension management and control that are demonstrated in this study have been shown in other settings such as in the UK (30) and Finland (31). The improvements are not only observed in developed settings.…”
Section: Discussionsupporting
confidence: 88%
“…In our survey as in many other studies [10,14-16,19-23] AH awareness and control were higher in women than in men, but the percentages of control indicate that women had a possibly better perception of hypertension-associated risks. In addition, some positive improvements in AH awareness, treatment and control were observed.…”
Section: Discussionsupporting
confidence: 69%
“…3 Population based studies have found that around two thirds of people with hypertension are either untreated or inadequately controlled, including many remain undiagnosed. [4][5][6] Many quantitative studies have published in knowledge, attitude and practice including adherence, whereas qualitative studies are subtle. The main aim of this study was to assess the knowledge of hypertensive patients about their disease in terms of causes, complications and barrier to get medications by in depth interview method.…”
mentioning
confidence: 99%